2019
DOI: 10.1038/s41390-019-0693-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of neonatal EEG background and neurodevelopment in full-term small for their gestational age infants

Abstract: BACKGROUND: Delayed brain function development in small-gestational-age (SGA) infants has been reported. We aimed to quantify rates of immature neonatal EEG patterns and their association with neurodevelopment in SGA full-term neonates. METHODS: Using a cohort design, 50 SGA (birthweight <10th percentile) and 44 appropriate-gestational-age (AGA) term neonates underwent continuous video-EEG recordings lasting >3 h. Seventy-three of them were assessed at 2-years-old using Bayley-III-Scales. For EEG analysis, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…There are two main types of brain injury in premature infants, namely, intracranial hemorrhage and periventricular white matter softening. Severe brain damage in premature infants can lead to death or moderate-to-severe neurodevelopmental disorders, including cerebral palsy, mental retardation, and vision and hearing impairment, and seriously affect the quality of life of preterm infants [ 4 , 5 ]. Therefore, the early evaluation and prevention of brain injury and its adverse neurological prognosis in preterm infants have become the focus of medical research in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main types of brain injury in premature infants, namely, intracranial hemorrhage and periventricular white matter softening. Severe brain damage in premature infants can lead to death or moderate-to-severe neurodevelopmental disorders, including cerebral palsy, mental retardation, and vision and hearing impairment, and seriously affect the quality of life of preterm infants [ 4 , 5 ]. Therefore, the early evaluation and prevention of brain injury and its adverse neurological prognosis in preterm infants have become the focus of medical research in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…In the three studies in this review that used the scale, 33 , 34 , 37 a lower performance was found in the assessed domains in the SGA group when compared to the AGA group, as it was not observed in the study by O’Neill et al 32 …”
Section: Discussionmentioning
confidence: 63%
“…Regarding the SGA classification, a Japanese study considered birth weight below the tenth percentile for gestational age (GA) and birth length below -2.0 standard deviation (SD) for GA, or birth weight below -2.0 SD for GA and length below the tenth percentile for GA. 31 In the other studies 29 , 30 , 32 37 only birth weight below the tenth percentile for GA was considered according to local standards, based on the uterine growth curve. 3 , 5 Some authors 30 reported that they disregarded height due to inaccuracies in the measurements at birth, following the evidence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations